Extent of Students' Practices as Digital Citizens in the 21st century - Salvacion Mata-Domingo; Nenita Guerrero (Research in Social Sciences and Technology- OpenED Network, 2018)
This study aims to determine the level or extent of practices on the norms or behaviors of the participants with regard to the use of technology. It is technically termed as digital citizenship. The descriptive survey method was utilized in this study. A researcher-made survey questionnaire patterned from an online article with slight modification is the main tool used in this paper. The research setting of this study is in one of the colleges in Muscat in the Sultanate of Oman. The participants are the two hundred randomly selected students who are officially enrolled in Level 5 and 6 in the Academic Year 2016-2017. The result of the study dwelled on the three main indicators namely: respect yourself and/or respect others; educate yourself and/or connect with others; and protect yourself and/or protect others. This findings revealed that different genders that are at different educational levels have diverse level or extent of norms that are applied when using a technology. As manifested by the participants it was found out that self-education and connection with others is practiced by them at an extent higher than their self- respect and respect to others. Furthermore, it can be concluded that the male is more sensible than female when it comes to self-education and/or connect with others as applied in use of technology. In addition, according to what was shown by most of the participants, protecting oneself or protecting others is generally at a lesser extent of practice by them. Some of the male and female participants are less conscious on what is meant by digital health and wellness.